Considerazioni a margine del “caso Piludu” fra princìpi costituzionali e pronunce giurisprudenziali in materia di rifiuto di trattamenti sanitari salvavita (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The article analyzes, under the point of view of the previous case-law, the recent assessment of the Cagliari Guardianship Court in a lawsuit concerning the petition of a patient, suffering from ALS, to stop life-prolonging treatment. In particular, the article firstly examines the right to give informed and actual refusal to a treatment side-by-side to the right to care planning future therapies for a situation of sudden incompetency (living wills), and then evaluates the necessity of an authorization by the guardianship court in order to stop the life-saving treatments on request of competent patients.
Keywords: End-of-life decision-making; Principle of autonomy; Refusal of medical treatments; Advance directives; Guardianship